Effect of tubular-typed charcoal height variations on efficiency in passive interfacial solar desalination - Pardiono, Tri Ramadhani; Jafri, Muhamad; Tarigan, Ben Vasco (Politeknik Negeri Lhokseumawe, 2024)
Passive solar desalination is a process of reducing the salt content of salt water to produce fresh water by utilizing solar heat. In recent years, interfacial heating has been proposed as an alternative to evaporation by creating localized heat on the water surface. Charcoal is an absorbent, heat storage, and wettability material, so the evaporation process not only occurs on the surface of seawater but also on the surface of the charcoal, which results from this wettability. The height of the charcoal indicates the distance the steam travels to reach the glass surface for the condensation process, thereby speeding up evaporation. The experiment was carried out in 4 single-slope-type basins using tubes filled with charcoal as high as 30, 40, and 50 mm for 8 hours in the sun. The results showed that adding heat-absorbing material to the basin was able to accelerate seawater to reach its boiling point so that it could evaporate. The temperature and humidity in each basin also have a similar changing trend where temperature is strongly influenced by solar radiation. The use of charcoal can also increase the rate of convection and evaporation heat transfer in the basin, as well as the maximum efficiency in basin 4 with an efficiency value of 56.40%, basin 2 at 53.17%, basin 3 at 51.62%, and basin 1 44.17%. Efficiency is obtained from the desalination efficiency equation, namely the ratio of the latent heat of vaporization to the solar energy entering the system